SISTEM PENGOLAHAN DATA PERNIKAHAN PADA KUA KECAMATAN TANJUNG TIRAM - Sahat Parulian Sitorus, Nurhasanah (PT.JNDI, JURNAL BIMA, 2023)
KUA (Religious Affairs Office) is a public institution that represents Islamic religious affairs to officially marry a couple (man and woman) in the eyes of the law in Indonesia. KUA is a public institution organized by the government which carries out some of the tasks of the Regency and City Ministry of Religion, especially in the field of Islamic religious affairs, Tanjung Tiram District, Batu Bara Regency. The duties of the Tanjung Tiram District KUA include marriage registration and reconciliation services in the Tanjung Tiram District location. Apart from providing good service to the community, it is also necessary to record marriage data and references that are integrated on an application basis. Based on data in the field, the process of recording marriages and reconciliations still uses paper media as data archives, so it takes a long time to search for data in making reports. The system for processing marriage registration data and making reports also makes it easier for people who want to register for marriage registration. The software system development uses Visual Basic as the programming language and Microsoft Access as the database. This application system can provide information regarding the marriage contract schedule and make it easier for the KUA head to report on the implementation of the marriage contract to make institutional policies.